The financing decision and its impact on the financial performance of the economic corporation case study SAIDAL Group (2015-2020)- - djemai, mohammed salah (Journal of Research in Finance and Accounting, 2026)
The objective of the study was to analyse the funding decision through the components of the financial architecture, namely, the ratio of total debt to private funds and the impact of the latter on financial performance, calculated by the ratios of financing, liquidity and earnings. Through the field study at the Sidal Complex during the period 2020-2015, the study found that there was a direct correlation between the financial upturn and the financing and liquidity ratios, and that there was no relationship between the ratio of the financial structure and both the asset earners, the financial earners and the commercial earners.